Neonatal Hypoxic-Ischemic Encephalopathy Yields Permanent Deficits in Learning Acquisition: A Preclinical Touchscreen Assessment - Maxwell, Jessie R.; Zimmerman, Amber J.; Pavlik, Nathaniel; Newville, Jessie C.; Carlin, Katherine; Robinson, Shenandoah; Brigman, Jonathan L.; Northington, Frances J.; Jantzie, Lauren L. (Frontiers in Pediatrics, 2020)
Neonatal hypoxic-ischemic encephalopathy (HIE) remains a common problem world-wide for infants born at term. The impact of HIE on long-term outcomes, especially into adulthood, is not well described. To facilitate identification of biobehavioral biomarkers utilizing a translational platform, we sought to investigate the impact of HIE on executive function and cognitive outcomes into adulthood utilizing a murine model of HIE. HIE mice (unilateral common carotid artery occlusion to induce ischemia, followed by hypoxia with a FiO2 of 0.08 for 45 minutes) and control mice were tested on discrimination and reversal tasks touchscreen tasks shown to be sensitive to loss of basal ganglia or cortical function, respectively. We hypothesized that the HIE injury would result in deficits in reversal learning, revealing complex cognitive and executive functioning impairments. Following HIE, mice had a mild discrimination impairment as measured by incorrect responses but were able to learn the paradigm to similar levels as control. During reversal, HIE mice required significantly more total trials, errors and correction trials across the paradigm. Analysis of specific stages showed that reversal impairments in HIE were driven by significant increases in all measured parameters during the late learning, striatal-mediated portion of the task. Together, these results support the concept that HIE occurring during the neonatal period results in abnormal neurodevelopment that persists into adulthood, which can impact efficient associated learning. Further, these data show that utilization of an established model of HIE coupled with touchscreen learning provides valuable information for screening therapeutic interventions that could mitigate these deficits to improve the long-term outcomes of this vulnerable population.